LSD1‐Demethylated LINC01134 Confers Oxaliplatin Resistance Through SP1‐Induced p62 Transcription in HCC. Issue 6 (5th October 2021) - Ma, Luyuan; Xu, An; Kang, Lei; Cong, Rui; Fan, Zhongyi; Zhu, Xiang; Huo, Nan; Liu, Wenpeng; Xue, Chunyuan; Ji, Quanbo; Li, Wenchao; Chu, Zhong; et al.
Abstract : Background and Aims: Oxaliplatin (OXA) is one of the most common chemotherapeutics in advanced hepatocellular carcinoma (HCC), the resistance of which poses a big challenge. Long noncoding RNAs (lncRNAs) play vital roles in chemoresistance. Therefore, elucidating the underlying mechanisms and identifying predictive lncRNAs for OXA resistance is needed urgently. Methods: RNA sequencing (RNA‐seq) and fluorescence in situ hybridization (FISH) were used to investigate the OXA‐resistant (OXA‐R) lncRNAs. Survival analysis was performed to determine the clinical significance of homo sapiens long intergenic non‐protein‐coding RNA 1134 (LINC01134) and p62 expression. Luciferase, RNA immunoprecipitation (RIP), chromatin immunoprecipitation (ChIP), and chromatin isolation by RNA purification (ChIRP) assays were used to explore the mechanisms by which LINC01134 regulates p62 expression. The effects of LINC01134/SP1/p62 axis on OXA resistance were evaluated using cell viability, apoptosis, and mitochondrial function and morphology analysis. Xenografts were used to estimate the in vivo regulation of OXA resistance by LINC01134/SP1/p62 axis. ChIP, cell viability, and xenograft assays were used to identify the demethylase for LINC01134 up‐regulation in OXA resistance. Results: LINC01134 was identified as one of the most up‐regulated lncRNAs in OXA‐R cells. Higher LINC01134 expression predicted poorer OXA therapeutic efficacy. LINC01134 activates anti‐oxidative pathway through p62 by recruiting transcription factor SP1 to the p62 promoter. The LINC01134/SP1/p62 axis regulates OXA resistance by altering cell viability, apoptosis, and mitochondrial homeostasis both in vitro and in vivo . Furthermore, the demethylase, lysine specific demethylase 1 (LSD1) was responsible for LINC01134 up‐regulation in OXA‐R cells. In patients with HCC, LINC01134 expression was positively correlated with p62 and LSD1 expressions, whereas SP1 expression positively correlated with p62 expression. Conclusions: LSD1/LINC01134/SP1/p62 axis is critical for OXA resistance in HCC. Evaluating LINC01134 expression in HCC will be effective in predicting OXA efficacy. In treatment‐naive patients, targeting the LINC01134/SP1/p62 axis may be a promising strategy to overcome OXA chemoresistance.